Audit Fee Stickiness, CEO Narcissism, and Tax Avoidance in IDX-Listed Manufacturing Firms (2020–2022) - Mira, Mira; Masrullah, Masrullah; Mursalim, Nur Ainun (Invoice : Jurnal Ilmu Akuntansi, 2025)
This study examines the relationship between audit fee stickiness, CEO narcissism, and tax avoidance in manufacturing firms listed on the Indonesia Stock Exchange (IDX) from 2020 to 2022. Audit fee stickiness occurs when changes in expected audit fees do not align proportionally with actual audit fee changes. CEO narcissism, characterized by excessive self-admiration and a strong desire for dominance, can influence corporate decision-making, including tax avoidance strategies. Tax avoidance, often viewed as strategic tax planning, aims to minimize corporate tax liabilities while complying with tax regulations. Using a quantitative approach, this study employs multiple regression analysis to assess the impact of CEO narcissism on tax avoidance and the moderating effect of audit fee stickiness. The findings indicate that narcissistic CEOs tend to engage in aggressive tax planning, increasing the likelihood of tax avoidance. Additionally, audit fee stickiness moderates this relationship, as firms with high audit fee stickiness exhibit lower levels of tax avoidance due to stronger auditor oversight. The study further reveals that tax savings from avoidance strategies affect cost stickiness, with implications for managerial decision-making. These results highlight the importance of understanding CEO personality traits in corporate governance and tax strategies. Regulators and auditors should consider CEO psychological factors when assessing tax compliance risks. Furthermore, firms should balance cost efficiency and ethical financial practices to maintain long-term sustainability and corporate reputation. This study contributes to the literature on tax avoidance, audit fee behavior, and the role of executive characteristics in financial decision-making.